Natural Compounds: A Hopeful Promise as an Antibiofilm Agent Against Candida Species - Shariati, Aref; Didehdar, Mojtaba; Razavi, Shabnam; Heidary, Mohsen; Soroush, Fatemeh; Chegini, Zahra (Frontiers in Pharmacology, 2022)
The biofilm communities of Candida are resistant to various antifungal treatments. The ability of Candida to form biofilms on abiotic and biotic surfaces is considered one of the most important virulence factors of these fungi. Extracellular DNA and exopolysaccharides can lower the antifungal penetration to the deeper layers of the biofilms, which is a serious concern supported by the emergence of azole-resistant isolates and Candida strains with decreased antifungal susceptibility. Since the biofilms’ resistance to common antifungal drugs has become more widespread in recent years, more investigations should be performed to develop novel, inexpensive, non-toxic, and effective treatment approaches for controlling biofilm-associated infections. Scientists have used various natural compounds for inhibiting and degrading Candida biofilms. Curcumin, cinnamaldehyde, eugenol, carvacrol, thymol, terpinen-4-ol, linalool, geraniol, cineole, saponin, camphor, borneol, camphene, carnosol, citronellol, coumarin, epigallocatechin gallate, eucalyptol, limonene, menthol, piperine, saponin, α-terpineol, β–pinene, and citral are the major natural compounds that have been used widely for the inhibition and destruction of Candida biofilms. These compounds suppress not only fungal adhesion and biofilm formation but also destroy mature biofilm communities of Candida. Additionally, these natural compounds interact with various cellular processes of Candida, such as ABC-transported mediated drug transport, cell cycle progression, mitochondrial activity, and ergosterol, chitin, and glucan biosynthesis. The use of various drug delivery platforms can enhance the antibiofilm efficacy of natural compounds. Therefore, these drug delivery platforms should be considered as potential candidates for coating catheters and other medical material surfaces. A future goal will be to develop natural compounds as antibiofilm agents that can be used to treat infections by multi-drug-resistant Candida biofilms. Since exact interactions of natural compounds and biofilm structures have not been elucidated, further in vitro toxicology and animal experiments are required. In this article, we have discussed various aspects of natural compound usage for inhibition and destruction of Candida biofilms, along with the methods and procedures that have been used for improving the efficacy of these compounds.